2010
DOI: 10.1111/j.1365-2133.2010.09652.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of transforming growth factor-β1 and oxidative stress in podoconiosis pathogenesis

Abstract: This is the first study, to our knowledge, to attempt to elucidate the molecular pathogenetic events in podoconiosis. We conclude that TGF-beta1 may have a pathogenetic role, with oxidative stress playing a minor role in the early stages of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 42 publications
0
12
1
Order By: Relevance
“…The odd of Podoconiosis was 3.85 times higher in the male gender. This finding is different from other scholarly findings ( 32 , 33 ). This might be due to the different exposure distribution of predictors of Podoconiosis in these areas.…”
Section: Discussioncontrasting
confidence: 99%
“…The odd of Podoconiosis was 3.85 times higher in the male gender. This finding is different from other scholarly findings ( 32 , 33 ). This might be due to the different exposure distribution of predictors of Podoconiosis in these areas.…”
Section: Discussioncontrasting
confidence: 99%
“…Release and transdermal uptake of a range of ions bound to pelotherapy clays has been demonstrated [16], so it is possible that ionic species adsorbed to clays of podoconiosis endemic areas are exchanged across the skin of the lower leg and foot. A study of the role of inflammatory biomarkers for development of podoconiosis has indicated increased anion (O 2 − ) and hydroxyl radicals (HO) in the early stages [17]. The major source of these peroxides was suggested to be activation and subsequent elimination of macrophages, which might relate to soil minerals with high oxidation properties.…”
Section: Discussionmentioning
confidence: 99%
“…Podoconiosis is thought to be the result of abnormal inflammatory responses to one or more mineral triggers. Little is known of the mediators involved in this inflammatory process, though transforming growth factor β may play a role [16]. We hypothesized that patients with podoconiosis might manifest an anemia of chronic disease, and that anemia might be more pronounced in the presence of anemia-causing intestinal helminths.…”
Section: Introductionmentioning
confidence: 99%